The Role of Fishermen's Wife in Increasing Family Income - Wilda Fesanrey; Samsia Umasugi; M Chairul Basrun Umanail0 (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2020)
The uncertainty of the income that the head of the fisherman's household in Namlea Village encourages his wife to work to meet family needs. The role of the fishermen's wife is needed because it affects the level of family income. This is what encourages researchers to conduct research with the aim of knowing how the role of fishermen's wives in increasing family income in Namlea Village, Buru Regency. The method used in this research is a survey method, which is an investigation that obtains facts from the existing symptoms of the role of fishermen's wives in Namlea Village, Namlea District, Buru Regency and analyzed by descriptive method. Sampling in this study using a purposive sampling method. This type of research is descriptive qualitative. Respondents taken in this study amounted to 18 people or 25% of the total population of 72 fishermen's wives. The domestic role of women, which are all activities carried out by fishermen's wives in maintaining fishermen's households, which consists of jobs such as cooking, washing, ironing, cleaning the house, and childcare are priceless. The public role of women is all the activities of fishermen's wives that generate income outside of their homes. Fishermen's wives are required to play a role in making a living by being involved in earning a living. The work that is done by the fishermen's wife is like selling fresh (raw) fish and processed fish (smoked fish). The results of this study indicate that 18 fishermen wife respondents show a contribution or proportion that affects the total income of the fishermen's family with the criteria classified as moderate, which means that it is quite influential in increasing family income and can meet family needs. This research can assist local governments in formulating policies related to improving fishermen's welfare through the active role of family members.